Identifying The Economic and Social Structure of The Yemeni Families by Using Multi variable Statistical Analysis - Hasan, Saeed; Tayoub, Mahmoud (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يعد علم الإحصاء الركيزة الأساسية التي تعتمد عليه العلوم التطبيقية بصفة عامة والعلوم الاجتماعية بصفة خاصة, وانطلاقاً من ذلك الدور لعلم الإحصاء وربط ذلك بدراسة وتحليل قضايا المجتمع, تناول هذا البحث تحديد الهيكل الاقتصادي والاجتماعي لأسر المجتمع اليمني وتحديد العوامل والأبعاد الاقتصادية والاجتماعي الفاعلة والمحددة لهذا الهيكل باستخدام الأساليب الإحصائية المتقدمة كطرق التحليل متعدد المتغيرات /CPA. وخلص هذا البحث إلى وجود عاملين: الأول: اقتصادي ارتبط به أربعة متغيرات هي: -درجة اقتناء السلع-نصيب الفرد الشهري-الإنفاق على الخدمات والرعاية الصحية-الإنفاق على التعليم. والثاني: اجتماعي يرتبط أيضاً بأربعة متغيرات هي: الحالة التعليمية-الحاجة العملية- درجة التزاحم داخل السكن- حالة المسكن. وتبين وجود أربعة متغيرات غير مرتبطة بأي من العوامل. Statistics is the fundamental base of the applied sciences in general and the social sciences in particular. Depending on this role of Statistics, and linking this to the study and analysis of society’s problems, in t his paper we study the economic and social structure of the families of the Yemeni society by identifying the criterion and the effective economic and social factors of this structure using advanced statistical method such as multivariable methods of Statistical Analysis. The research stresses the existence of two factors: 1. An economic factor to which four variables are linked: - The degree of possession of goods - per capita monthly - Spending on services and health care - spending on education. 2. A social factor is also linked to four variables: the educational situation - the daily need - a scramble inside the housing - house situation. Moreover, we have seen the presence of four variables not bound by any of the factors